2019
DOI: 10.1111/cmi.13027
|View full text |Cite
|
Sign up to set email alerts
|

Eimeria tenellaROPkinaseEtROP1induces G0/G1 cell cycle arrest and inhibits host cell apoptosis

Abstract: Coccidia are obligate intracellular protozoan parasites responsible for human and veterinary diseases. Eimeria tenella, the aetiologic agent of caecal coccidiosis, is a major pathogen of chickens. In Toxoplasma gondii, some kinases from the rhoptry compartment (ROP) are key virulence factors. ROP kinases hijack and modulate many cellular functions and pathways, allowing T. gondii survival and development. E. tenella's kinome comprises 28 putative members of the ROP kinase family; most of them are predicted, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 57 publications
(85 reference statements)
3
35
0
Order By: Relevance
“…The distribution of Et-ROPK-Eten5-A and Et-GRA12 in sporozoites and merozoites of E. tenella was assessed using immunofluorescence and a mouse anti-rEt-ROPK-Eten5-A antibody and mouse anti-Et-GRA12 antibody. Et-ROPK-Eten5-A was distributed in the apical area of sporozoites, which was similar to the localization of Et-ROP1 protein [34]. A previous report showed that free second-generation merozoites had a long, slender body with two rhoptries at the apical pole [35].…”
Section: Discussionsupporting
confidence: 79%
“…The distribution of Et-ROPK-Eten5-A and Et-GRA12 in sporozoites and merozoites of E. tenella was assessed using immunofluorescence and a mouse anti-rEt-ROPK-Eten5-A antibody and mouse anti-Et-GRA12 antibody. Et-ROPK-Eten5-A was distributed in the apical area of sporozoites, which was similar to the localization of Et-ROP1 protein [34]. A previous report showed that free second-generation merozoites had a long, slender body with two rhoptries at the apical pole [35].…”
Section: Discussionsupporting
confidence: 79%
“…Sporozoites ready to invade show overexpression of five different surface antigens (SAGs) which are important proteins in the recognition and attachment of the host cell (Tabares et al, 2004 ), as well overexpression of apical membrane antigen-1 (AMA1) and three rhoptry neck proteins (RONs) which are components of the moving junction, an essential structure for the invasion of the host cell in many Apicomplexa parasites (Besteiro et al, 2011 ). Three rhoptry kinases (ROPK), essential for intracellular survival through interaction with host proteins (Diallo et al, 2019 ), are also overexpressed by these pre-invading sporozoites. Once sporozoites have invaded the host cell (4 hpi), a switch in repertoire of SAG protein expression was observed, with four different SAGs found overexpressed here.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we additionally analysed typical markers of senescence as cell cycle-related status in E. bovis -infected cells. So far, parasite-triggered alteration of the host cellular cell cycle is a well-known feature acting on different phases and molecules of the cell cycle in a parasite-specific and even host cell type-specific fashion (Bouzahzah et al ., 2008 ; Brunet et al ., 2008 ; Molestina et al ., 2008 ; Wiens et al ., 2014 ; Kim et al ., 2016 ; Diallo et al ., 2019 ; Velásquez et al ., 2019 ). Thus, L. amazonensis interferes early in cell cycle by G 0 /G 1 phase arrest (Kuzmenok et al ., 2005 ), Encephalitozoon infections induce an accumulation of host cells in the S phase (Scanlon et al ., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a cell type-specific manner, T. gondii was shown to induce a shift from G 0 /G 1 through the S phase with the accumulation of host cells in the S phase at the G 2 /M boundary in human foreskin fibroblasts, to trigger host cellular arrest in the G 2 phase in a human trophoblast cell line, in human dermal fibroblasts and in an L6 rat myoblast cell line (Brunet et al ., 2008 ; Kim et al ., 2016 ) or to mediate a G 2 /M arrest in primary bovine endothelial cells (Velásquez et al ., 2019 ). Referring to Eimeriidae, the only available report indicated a G 0 /G 1 arrest in E. tenella -infected host cells (Diallo et al ., 2019 ). In the case of Plasmodium spp., Plasmodium falciparum infections affected mitosis and led to a lack of cell division in HepG2 cells (Hanson et al, 2015 ) but cell cycle-dependent reactions neither played a role in Plasmodium berghei - or Plasmodium yoelii -infected mouse models nor in P. falciparum -infected primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation